Procidentia incarcerated by multiple vesical calculosis: vaginal cystolithotomy for cystolithiasis - Dhakal, B; Rana, A (Journal of Institute of Medicine Nepal, 2007)
Background: Incarceration of procidentia from multiple calculi in the cystocele in a post menopausal lady with long standing duration of pelvic organ prolapse treated by vaginal cystolithotomy, vaginal hysterectomy and pelvic floor repair is reported herewith. Key words: procidentia, cystolithiasis, cystocele, cystolithotomy, pelvic organ prolapse. The full text of this paper is available at Journal of Institute of Medicine website